Isoenzymes of Glutamate Dehydrogenase in Plants - Yue, S. B. (1969)
Glutamate dehydrogenase of several different plants was resolved by polyacrylamide gel electrophoresis into separate molecular forms and the isoenzymic patterns detected by the tetrazolium technique were compared. The number of isoenzymes and their electrophoretic mobilities varied among the different plants studied. The isoenzymes were found to have the same coenzyme specificity and to localize in the mitochondrial fraction of the cell in all the plants examined. Electrophoretic heterogeneity in tissue homogenates was observed in some of the plants studied. The pattern of isoenzymes of mungbean hypocotyl was followed and shown to change during germination.